The blurred cut-off frequency of acoustic horns - ZAMORSKI, Tomasz (Archives of Acoustics, 1981)
On the basis of discussion of the Webster equation the conditions and possibilities of a blurred cut-off frequency for horns of arbitrary geometry were analyzed. The transmission properties of horns in the blurred region were discussed. Subsequently the blurred cut-off frequency was considered for hyperbolic horns of annular cross-section.